Negative Regulation of DNA Repair Gene (ung) Expression by the CpxR/CpxA Two-Component System in Escherichia coli K-12 and Induction of Mutations by Increased Expression of CpxR - Ogasawara, Hiroshi (American Society for Microbiology, 2004)
In Escherichia coli K-12 overexpressing CpxR, transcription of the ung gene for uracil-DNA glycosylase was repressed, ultimately leading to the induction of mutation. Gel shift, DNase I footprinting, and in vitro transcription assays all indicated negative regulation of ung transcription by phosphorylated CpxR. Based on the accumulated results, we conclude that ung gene expression is negatively regulated by the two-component system of CpxR/CpxA signal transduction.